2014
DOI: 10.1093/treephys/tpu042
|View full text |Cite
|
Sign up to set email alerts
|

Metal (Pb, Zn and Cu) uptake and tolerance by mangroves in relation to root anatomy and lignification/suberization

Abstract: Metal pollution has been widely reported in mangrove wetlands; however, the mechanisms involved in metal detoxification by mangroves are still poorly understood. This study aimed to investigate the possible function of root anatomy and lignification/suberization on metal uptake and tolerance in seedlings of six species of mangroves. The results revealed that the three rhizophoraceous species (Bruguiera gymnorrhiza (L.) Poir, Kandelia obovata Sheue, Liu & Yong and Rhizophora stylosa Griff) consistently exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…In contrast, 28.3% of SAHA-upregulated genes are high salinity stress-responsive (Figure S2A), and only 27 SAHA-upregulated genes were upregulated by high-salinity stress (2 and/or 24 h NaCl treatment; Table 6). In mangrove plants, lignin accumulation functions in blocking metal-ion influx with higher suberization, suggesting that lignification can prohibit ions from flowing inside (Cheng et al, 2014). We analyzed the following three genes that are believed to play critical roles in regulating lignin accumulation: L-phenylalanine ammonia lyase ( PAL ), cinnamyl alcohol dehydrogenase ( CAD ), and caffeic acid 3-Omethyltransferase ( COMT ) genes (Whetten and Sederoff, 1995; Ma and Xu, 2008; Nguyen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 28.3% of SAHA-upregulated genes are high salinity stress-responsive (Figure S2A), and only 27 SAHA-upregulated genes were upregulated by high-salinity stress (2 and/or 24 h NaCl treatment; Table 6). In mangrove plants, lignin accumulation functions in blocking metal-ion influx with higher suberization, suggesting that lignification can prohibit ions from flowing inside (Cheng et al, 2014). We analyzed the following three genes that are believed to play critical roles in regulating lignin accumulation: L-phenylalanine ammonia lyase ( PAL ), cinnamyl alcohol dehydrogenase ( CAD ), and caffeic acid 3-Omethyltransferase ( COMT ) genes (Whetten and Sederoff, 1995; Ma and Xu, 2008; Nguyen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…HM ions can bind to the functional groups of cell wall components, such as cellulose, hemicellulose, lignin, and pectin (Chen, Liu, Wang, Zhang, & Owens, ; Parrotta, Guerriero, Sergeant, Cai, & Hausman, ). Some plants can enhance their lignin biosynthesis in response to HM exposure, thereby suggesting that lignin in plant cell walls plays a role in sequestering HMs (Cheng et al, ; Elobeid, Gobel, Feussner, & Polle, ). By HM sequestration in root cell walls, the entry of HMs into the protoplasts can be reduced, thereby alleviating the toxicity of HMs in plant cells.…”
Section: Physiological and Molecular Mechanisms Of Hm Accumulation Inmentioning
confidence: 99%
“…Keshavarz et al (2012) revealed that the Cd and V were negligible in sediments surrounding roots zones of A. marina and R. mucronata, whereas Pd concentrations were higher compared to leaves and roots. Cheng et al (2014) revealed that the three rhizophoraceous species (B. gymnorrhiza (L.) Poir, K. obovata Sheue, Liu and Yong, and R. stylosa (Griff) consistently exhibited higher metal (Pb, Zn and Cu) tolerances than the three pioneer species [Aegiceras corniculatum (Linn.) Blanco, Acanthus ilicifolius L. and A. marina (Forsk)].…”
Section: Heavy Metal Exposurementioning
confidence: 99%